Uma ferramenta 3D, via web, para dimensionamento de seções retangulares de concreto armado com esboço da armadura - Rogerio Pedrosa Sales (2010)
The technological development has expanded the use of computers in education worldwide. In structural engineering courses it is no different: many professors provide their students computer programs which help them do the necessary calculations to solve problems. However, these programs are designed for professional engineers and not students. In this scenario and also to assist professors teach reinforced concrete courses, this dissertation presents computational tools, accessed at Internet, for designing and detailing rectangular reinforced concrete sections subjected to bending, combined flexure and axial forces and shear. NBR 6118 (2007) criteria are employed herein. A dynamic 3D tool is used in the detailing scheme which allows students view the designed concrete sections from different angles.